Analisis Manajemen Keuangan UMKM Perikanan di Desa Terapung Kabupaten Buton Tengah: Pendekatan Kuantitatif dan Kualitatif - Rusdin Rusdin; Ismail Failu; Deki Pardana (DE FACTO : Journal Of International Multidisciplinary Science, 2026)
Fisheries Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economic development of coastal communities; however, financial management practices remain limited. This study aims to analyze the financial management practices of anchovy-processing MSMEs in Terapung Village, Mawasangka District, Central Buton Regency. A mixed-methods case study was conducted involving all 11 MSMEs as the census population. Financial data from January to June 2026 were analyzed using descriptive and inferential statistics. The findings indicate an average annual revenue of IDR 3.04 billion and a net profit margin of 32.35%. Strong positive correlations were found between initial capital and annual revenue (r = 0.991; p < 0.001), and business experience and net profit (r = 0.952; p < 0.001). Most respondents (81.82%) neither maintained formal financial records nor accessed People's Business Credit (KUR). Strengthening financial management capacity, expanding inclusive financing, and providing technical assistance are essential to enhance MSME sustainability.